The 25th Venice Art Biennale and the Avant-garde Retrospective Exhibitions Designed by Carlo Scarpa: Palazzo Centrale as a Space of International Dialogue between Italy and France - Letizia Giardini (OBOE)
This paper aims to demonstrate how Palazzo Centrale’s main hall in the Giardini became a space for dialogue and cooperation between Italy and France during the 25th Venice Art Biennale. The two countries jointly developed a retrospective narrative on Fauvism, Cubism and Futurism, with a display designed by Carlo Scarpa.